2016
DOI: 10.1167/iovs.16-20303
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy Clinical Trials for SYL1001, a Novel Short Interfering RNA for the Treatment of Dry Eye Disease

Abstract: These trials achieved their primary endpoints of identifying the most effective dose of SYL1001 (1.125%). SYL1001 showed a large safety margin and may provide novel therapeutic opportunity for the relief of dry eye. (ClinicalTrials.gov numbers, NCT01438281, NCT01776658, and NCT02455999.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 24 publications
0
53
1
Order By: Relevance
“…In a large, placebo‐controlled clinical trial, SYL1001 demonstrated significant improvements in visual analogue scale scores and excellent tolerability (Benitez‐Del‐Castillo et al. ).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…In a large, placebo‐controlled clinical trial, SYL1001 demonstrated significant improvements in visual analogue scale scores and excellent tolerability (Benitez‐Del‐Castillo et al. ).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…* P < 0.05 compared with control, unless specified. [28,29]. It is possible to apply silencing SPARC in vivo with a similar technique, and the in vivo application of silencing SPARC in patients receiving filtering surgery is an important researching field of our future study.…”
Section: Discussionmentioning
confidence: 99%
“…QPI‐1002 and QPI‐1007 were developed by Quark Pharmaceuticals, for the treatment of delayed graft function (phase 3) and acute kidney injury (phase 2), as well as nonarteritic anterior ischemic optic neuropathy (phase 3) and acute primary angle closure glaucoma (phase 2), by targeting p53 and caspase 2, respectively. SYL1001 was developed by Sylentis for the treatment of ocular pain and dry eye syndrome, by targeting transient receptor potential cation channel subfamily V member 1 (TRPV1) …”
Section: Performance Of Sirna Therapy In Clinical Trailsmentioning
confidence: 99%